Retrospection, Regret, and Contingency in Dickens’s Late Midlives - McAllister, David (Age, Culture, Humanities: An Interdisciplinary Journal, 2021)
This essay explores Dickens’s representations of male anxieties over aging and argues both that contingency—a character’s dawning recognition that their life might have been otherwise—haunts Dickens’s midlife narratives and that a developing cultural awareness of midlife as a life-stage is central to the Victorian fascination with unlived lives. It traces developments in Dickens’s own sense of midlife’s particularity to two sources: a recognition of the bodily changes that accompany the process of aging (such as his own graying hair, which he sought to disguise cosmetically through hair and moustache dyes) and his membership of a generation whose life chances were determined by a demographic bulge caused by a rapid expansion of Britain’s middle-aged and elderly population. Both of these circumstances engender an overwhelming sense of regret in the aging protagonists of novels such as David Copperfield (1849-1850), Great Expectations (1860-1861), and Our Mutual Friend (1864-1865), whose midlives are spent thinking, and sometimes writing, about the youthful choices that shaped their later lives. It is only with the publication of the late portmanteau tale “Mugby Junction” that Dickens finds himself able to imagine a midlife in which the aging individuals possess agency and are empowered to cast off the determining and contingent events of their Bildungsroman narratives and engage in the processes of unbecoming and self-renewal.